2017
DOI: 10.4238/gmr16029643
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence among corn hybrids and combining ability for agronomic and bromatological traits of silage

Abstract: ABSTRACT.We assessed the impact of genetic divergence and the ability to combine corn hybrids used for the production of silage on the agronomic and bromatological traits of silage quality. We evaluated 18 corn hybrids used as genitors in a circulant diallel scheme in which each genitor hybrid participated in 9 hybrid combinations, and evaluated 100 treatments [18 genitor hybrids, 81 diallelic hybrids, and a commercial check hybrid (DKB330)] in a triple lattice 10 x 10 experimental design in two environments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The DNA code is the template which directs the organization and function of a complete organism by directing synthesis of range of macromolecules (1,2) . Repetitive DNA sequences gradually gets accumulated into the genomes during the course of evolution because of non-repairable variations arising from events like mutations, slipped strand mispairing and unequal crossing (3,4) . The term repetitive DNA sequences collectively represent the DNA fragments which are present in multiple copies into the genomes (5) .…”
Section: Introductionmentioning
confidence: 99%
“…The DNA code is the template which directs the organization and function of a complete organism by directing synthesis of range of macromolecules (1,2) . Repetitive DNA sequences gradually gets accumulated into the genomes during the course of evolution because of non-repairable variations arising from events like mutations, slipped strand mispairing and unequal crossing (3,4) . The term repetitive DNA sequences collectively represent the DNA fragments which are present in multiple copies into the genomes (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variability related to forage yield and quality is a premise for the success of maize-forage breeding programs (Guerrero et al, 2014). Gralak et al (2017) reported the existence of variability in commercial hybrids regarding the quality of forage, and Barrière et al (2010) showed that superior genotypes could be selected from already improved ones. Despite this variability, breeding programs have mainly focused on genotypes with high grain and dry matter yields.…”
Section: Introductionmentioning
confidence: 99%